2017
DOI: 10.1155/2017/7258607
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Height-Weight Difference Index and Body-Fat Percentage Estimated by Bioelectrical Impedance Analysis in Thai Adults

Abstract: Introduction The height-weight difference index (HWDI) is a new indicator for evaluating obesity status. While body-fat percentage (BF%) is considered to be the most accurate obesity evaluation tool, it is a more expensive method and more difficult to measure than the others. Objective Our objectives were to find the relationship between HWDI and BF% and to find a BF% prediction model from HWDI in relation to age and gender. Method Bioelectrical impedance analysis was used to measure BF% in 2,771 healthy adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Nuttall (2015) observed an age-related wide range of BMI values in Minnesota, USA. From a study in Thailand, Juntaping et al (2017) suggested that the height-weight difference index could be an easy-touse obesity evaluation tool that could help awareness of underweight and obesity conditions. Bhaskaran et al (2018) observed in the UK that higher BMI was associated with overall mortality and most specific causes of death, while lower BMI was associated with increased mortality risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuttall (2015) observed an age-related wide range of BMI values in Minnesota, USA. From a study in Thailand, Juntaping et al (2017) suggested that the height-weight difference index could be an easy-touse obesity evaluation tool that could help awareness of underweight and obesity conditions. Bhaskaran et al (2018) observed in the UK that higher BMI was associated with overall mortality and most specific causes of death, while lower BMI was associated with increased mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the body weight, height and BMI from Israel (Ginsburg et al, 1998) and Minnesota, USA (Nuttall, 2015) showed that BMI could be used for defining anthropometric height/weight characteristics in adults, which could also be used as a risk factor assessment for several health issues. Instead of BMI, however, Juntaping et al (2017) used a height-weight difference index (HWDI) in Thailand as a new indicator for evaluating obesity status. Furthermore, Bhaskaran et al (2018) demonstrated in a study in the UK that BMI had J-shaped associations with overall mortality and most specific causes of death, whereas lower BMI was associated with increased mortality risk.…”
Section: Inheritedmentioning
confidence: 99%
“…This paper illustrates the study of analyzing the influence of nutrition and sports on height and weight of male and female students. Some articles related to this issue such as (Islam et al, 2017), (Juntaping et al, 2017). The survey was conducted at an elementary school among the students of 6-11-year-old.…”
Section: Introductionmentioning
confidence: 99%
“…women considered as obese (Lobman, Houtkooper, & Going, 1997;Swainson et al, 2017;WHO, 1995), because BMI is not considered a good measure of obesity for Asian (Hingorjo, Syed, & Qureshi, 2009). Therefore, percent body fat is considered a reliable and accurate tool to measure obesity (Juntaping et al, 2017), particularly for Pakistani population percent body fat is a better scale to measure obesity as compared to BMI (Fatima, Rehman, & Chaudhry, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The South Asian have higher percent body fat (Misra et al, 2014) generally, while comparing with gender reference women significantly greater percent body fat as compared to male (Dias et al, 2016;Ilman, Zuhairini, & Siddiq, 2016;Juntaping et al, 2017;Jackson et al, 2002), but comparing within same gender the Asian women have higher body fat as compared to white (Deurenberg, Yap, & Van Staveren, 1998;Küpper et al, 1998;, Chinese (Ntuk et al, 2014), Norwegian (Falch, & Steihaug, 2000), and American women (Kamath et al, 1999).…”
Section: Introductionmentioning
confidence: 99%